2017
DOI: 10.1155/2017/3701740
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cyclic Loading on Chloride Diffusivity and Mechanical Performance of RC Beams under Seawater Corrosion

Abstract: An experimental study was conducted to investigate the impact of cyclic loading on the mechanical performance and chloride diffusivity of RC beams exposed to seawater wet-dry cycles. To induce initial damage to RC beam specimen, cyclic loading controlled by max load and cycles was applied. Then beam specimens underwent 240 wet-dry cycles of seawater. Results show that the chloride content increased as max load and cycle increased. The chloride content at steel surface increased approximatively linearly as aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Shen [84] found that, under the combined effect of fatigue load, wet and dry cycles, and Cl − erosion, the cracking of the concrete's protective layer was a slow process that develops from the inside out, with reinforcement corrosion causing cracks to develop from the inside towards the concrete surface; the fatigue load effect caused the pores to open and periodically, allowing Cl − to be adsorbed into the reinforcement on the side away from the protective layer. Pang [85] found that the residual yield load and ultimate load of beam specimens of RC decreased with increasing the maximum stress level of fatigue load after a cyclic load and 240 wet and dry cycles tests, and they concluded that the maximum stress level had an adverse effect on the yield load and ultimate load capacity, an effect that was greater than the effect of changing the number of cycles. Hua [86] simulated the actual working conditions of RC bridge structures in a coastal environment and undertook wet and dry cycles of seawater with a dry-wet ratio of 7:1 for 180 days at different stress levels and different numbers of fatigue cycles to determine the Cl − content of concrete in the tension and compression zones.…”
Section: Durability Of Concrete Under Dry-wet Cycles Fatigue Load And...mentioning
confidence: 99%
“…Shen [84] found that, under the combined effect of fatigue load, wet and dry cycles, and Cl − erosion, the cracking of the concrete's protective layer was a slow process that develops from the inside out, with reinforcement corrosion causing cracks to develop from the inside towards the concrete surface; the fatigue load effect caused the pores to open and periodically, allowing Cl − to be adsorbed into the reinforcement on the side away from the protective layer. Pang [85] found that the residual yield load and ultimate load of beam specimens of RC decreased with increasing the maximum stress level of fatigue load after a cyclic load and 240 wet and dry cycles tests, and they concluded that the maximum stress level had an adverse effect on the yield load and ultimate load capacity, an effect that was greater than the effect of changing the number of cycles. Hua [86] simulated the actual working conditions of RC bridge structures in a coastal environment and undertook wet and dry cycles of seawater with a dry-wet ratio of 7:1 for 180 days at different stress levels and different numbers of fatigue cycles to determine the Cl − content of concrete in the tension and compression zones.…”
Section: Durability Of Concrete Under Dry-wet Cycles Fatigue Load And...mentioning
confidence: 99%